Foreing Pedagogical Experience as a Factor of Modernization of the Ukraininan Teacher Training: Historical Outlook - O’smuk, Nataliya (Pedagogical Discourse, 2013)
In the article the application of experience of foreign Reformation pedagogics in the process of national teacher training modernization is characterized. The focus is on the contextual, organizational and methodological foreign innovations that were used by Ukrainian teachers. The role of foreign experience in the professional development of national teachers is stated. The key tasks of educational sphere in retrospective measuring of state documents are revealed. It is noted that general pedagogical preparation of pedagogues provides for mastering of the knowledge in pedology, physiology, anatomy, hygiene, and substantial component of these disciplines were ideas and views of the representatives of reformatory pedagogics – D. Dewey, R. Seidel, G. Kerschensteiner, M. Montessori, P. Natorp, S.Hall and others, interpreted by Soviet pedagogues. It is proved that innovations of reformatory pedagogics are the factors of modernization of the system of professional preparation of teachers.